EFFECT OF ENVIRONMENTAL PARAMETERS TO PURSE SEINE CATCHES IN BALI STRAIT - I Gede Pasek Zendra Barwana; Ersti Yulika Sari; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study was conducted in the Bali strait held from 2 to 16 April 2014 aimed to study the effect of environmental parameters on purse seine catches in the Bali strait such as temperature, salinity, current speed, depth, and pH , and the type of fish caught in the waters of the Bali strait. The method used in this research is the method of experimental fishing that by measuring and observing directly the environmental parameters in which it operates Purse Seine. The data collected in this study were: temperature, salinity, current speed, depth, and pH, and the type of fish caught. The catch and the measurement of these parameters are collected and then tabulated into a table and analyzed.The observation of environmental parameters during the study is the temperature range between 26-280 C, salinity ranges between 30-33 0/00, currents ranging from 0.3 to 0.5 m/s, water depths ranging from 64-78 m , and the pH of the water ranges from 7 - 8. The type of fish that were caught at Bali Strait is Sarden (Sardinella lemuru), mackerel scad (Decapterus mackarellus), and swordfish (Euthynnuss affinis).Keywords: Purse Seine, Bali strait, Environmental Parameters